A study of the expression and cellular function of the human FAM111B gene - Rhoda, Cenza (Department of Medicine, 2022)
POIKTMP, a multi-systemic fibrosing disease, results from mutations in the human FAM111B gene. Studies have also suggested high expression of this gene in cancers. Despite rising interest in the pathological effects of FAM111B mutations and overexpression of FAM111B, knowledge of the physiological role of this gene remains limited. Therefore, this study sought out to provide insights into the cellular function of FAM111B and to investigate the pathological effect of the FAM111B Y621D mutation. First, bioinformatics studies coupled with quantitative PCR and Western blots analysis were employed to assess FAM111B gene and protein expression in cancerous and non-cancerous cell lines. Subsequently, FAM111B gene expression was downregulated and upregulated in the human fibrosarcoma (HT1080) cell line by RNA-interference mediated gene silencing and recombinant gene expression technologies. The effect of these FAM111B dysregulations was studied using cellbased functional assays: proliferation, apoptosis, migration, and invasion assays. Furthermore, the functional pathways and interacting proteins of the FAM111B protein was determined using mass spectroscopy proteomics. Finally, preliminary studies in a POIKTMP patient-derived fibroblasts were attempted to recapitulate the results obtained using the HT1080 cell line. The results from this study indicated that FAM111B gene and protein overexpression occurs in cancer cells. Second, the depletion of FAM111B suggests a decelerated rate of cell proliferation and migration (14%), and increased apoptosis (1.4-fold). Conversely, overexpression of FAM111B resulted in a marked reduction in apoptosis (3-fold) and increased cell migration by 27 %, howbeit, no evidence of increased proliferation. Furthermore, Y621D FAM111B mutant cells showed reduced expression of FAM111B, decreased apoptosis (1.1-fold), cellular invasion (24%), and indicates an increase in cell proliferation and migration (18 %). The proteomics data suggested wild-type FAM111B interacts with HSP7C, a molecular chaperone, which alongside BAG3 and BCL2 to minimise apoptosis. Similarly, Y621D's interaction with G3V3W4, a component of the 20S proteasome complex involved in the proteolytic degradation of damaged proteins, may suggest the rapid clearance of this mutant protein.